POTENSI EKONOMI PENGGUNAAN BAHAN BAKAR MINYAK (Studi Kasus Universitas Diponegoro) - Indriani, Astiwi (P4M STIE Putra Bangsa, 2018)
This research want to investigate the economic potential of the use of fuel oil with research object at Diponegoro University. This research was conducted to know the potential of oil fuel usage in the campus area, the potential cost to fulfill the requirement of fuel oil and analyze the influence of the number of vehicle and the type of vehicle variable to the fuel consumption as well as the average difference of fuel consumption between the type of motorcycle and cars.The analysis technique used is quantitative descriptive analysis to find out the potential use and cost of fuel oil; also used multiple linear regression analysis and t-test different to analyze average difference of fuel consumption between motorcycle and car.The results of the analysis show that the potential use of fuel reaches 1987,7 liters for the nearest distance and 5331,5 liters for the furthest distance with potential cost of each reach 13 million rupiah and 35 million rupiah every 5 hours/week. Show that campus has a very high potential in the absorption of fuel. Then the percentage of vehicle users is mostly contributed by vehicles with vehicle code : H (42%), B (10%), and K (9%). The Results of multiple linear regression analysis with t test showed that the number of vehicles and vehicle types variable partially have a significant positive effect on the use (consumption) of fuel. Adjusted R square value of 94.7% and the rest 5.3% is influenced by other factors. T-test different results indicate that there are differences in fuel consumption between types of motorcycle and cars.Keywords: Number of vehicles, Type of Vehicle, Economic Potential of Fuel Oil Usage.